A New Aromatic Compound from Edible Flavouring Herb and Its Bioactivity - Choudhury, Ratna; Bhaumik, Pradip; De, Biplab (Asian Journal of Chemistry, 2014)
Tetrahydro-5-(hydroxymethyl)-6-(1,2-diphenylvinyl)-2H-pyran-2,3,4-triol having CNS depressant property was isolated by column chromatography from the leaves of an edible flavouring herb and was identified by IR, 1H, 13C NMR and LC-MS.